Central African Republic : Enhanced Initiative for Heavily Indebted Poor Countries; Completion Point Document and Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper focuses on Central African Republic's (CAR) completion point under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) and debt relief under the Multilateral Debt Relief Initiative (MDRI). In the view of International Development Association (IDA) and IMF staff, CAR has made satisfactory progress in meeting the requirements to reach the completion point. All the floating triggers have been fully implemented. Upon reaching the completion point under the enhanced HIPC Initiative, CAR will also qualify for additional debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet